2002
DOI: 10.1177/026988110201600206
|View full text |Cite
|
Sign up to set email alerts
|

Nimodipine prevents scopolamine-induced impairments in object recognition

Abstract: The effects of acute administration of the dihydropyridine calcium channel antagonist, nimodipine, were studied on the actions of scopolamine in the object recognition test. Scopolamine at 0.125 mg/kg decreased the difference in the time spent exploring novel and familiar objects when given either 15 min before, or immediately after, exposure to objects. Administration of nimodipine at 10 mg/kg, or 1 mg/kg, at the same time as the scopolamine completely prevented the deleterious effects on memory in this task.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
1
9
0
1
Order By: Relevance
“…reported that the familiarity discrimination was impaired by scopolamine administration before acquisition but not after acquisition. It was also reported that scopolamine decreased the difference in the time spent exploring novel and familiar objects either by administration 15 min before or by administration immediately after exposure to objects, suggesting scopolamine deteriorates acquisition and consolidation phases (Norman et al, 2002). Consistent with the previous report, we also observed that scopolamine impaired those memory phases, although the doses and the time points used are slightly different.…”
Section: Discussionsupporting
confidence: 91%
“…reported that the familiarity discrimination was impaired by scopolamine administration before acquisition but not after acquisition. It was also reported that scopolamine decreased the difference in the time spent exploring novel and familiar objects either by administration 15 min before or by administration immediately after exposure to objects, suggesting scopolamine deteriorates acquisition and consolidation phases (Norman et al, 2002). Consistent with the previous report, we also observed that scopolamine impaired those memory phases, although the doses and the time points used are slightly different.…”
Section: Discussionsupporting
confidence: 91%
“…Scopolamine is so well-established as an amnestic drug that it is often used as a model to induce a memory deficit which then a potential promnestic agent may redress (e.g., Norman, Brooks, Hennebry, Eacott, & Little, 2002). In rats, systemic or central administration of this drug impairs performance in several hippocampus-dependent tasks including the Morris water maze (Herrera-Morales, Mar, Serrano, & Bermudez-Rattoni, 2007; Janas et al, 2005; von Linstow Roloff, Harbaran, Micheau, Platt, & Riedel, 2007), the radial arm maze (Masuoka, Fujii, & Kamei, 2006; Mishima et al, 2000), spatial alternation in a T-maze (Givens & Olton, 1995), contextual fear conditioning (Anagnostaras, Maren, Sage, Goodrich, & Fanselow, 1999; Wallenstein & Vago, 2001) and spatial discrimination task (Carli, Luschi, & Samanin, 1997).…”
Section: What Are the Key Functions Of Acetylcholine In Memory?mentioning
confidence: 99%
“…The majority of these NK1R-expressing interneurons are cholinergic (Gerfen, 1991), but some are GABAergic (NPY/somatostatin (SOM)/NOS-expressing) (Kawaguchi et al, 1995;Li et al, 2002). Nifedipine-sensitive (L-type) channels are expressed by striatal neurons where they are involved in corticostriatal plasticity (Norman et al, 2002;Bonsi et al, 2004). These channels have been linked to periodic burstfiring of cholinergic interneurons (Goldberg and Wilson, 2005;Goldberg et al, 2009), and nifedipine attenuates acetylcholine efflux (Sanz et al, 2000).…”
Section: Effects Of Nifedipine On Behavior In the 5-csrttmentioning
confidence: 99%